Synergistic effect of fast extrusion furnace (FEF) black on viscosity and rheological properties of ethylene propylene diene monomer vulcanizate. Issue 2 (1st February 2023) - Sivakumar, A. R.; Baskaran, R.; Babu, B. Gurukarthik; Murugesan, A.
Abstract: An investigation is made on vulcanizates based Ethylene propylene diene monomer (EPDM) rubber which is prepared by incorporating 30 phr of cellulose short fibres along with different loading levels of fast extrusion furnace black (FEF) at an increment level of 20 phr in two roll mill. EPDM rubber was found as an attractive candidate for the thermal insulation of case-bonded SRM due to the advantages such as low specific gravity, improved ageing properties, and longer shelf life. This research provides theoretical and experimental characterisation for the friction behaviours of EPDM rubber. The effect of FEF on viscosity and rheological properties of various EPDM compounds such as C1–C8 were fairly investigated using the Monsanto moving die Rheometer (MDR 2000), and Mooney viscometer. The curing characteristics like TS2, TS5, ML, MH, cure time (TC90), and viscosity of various EPDM compounds were extensively determined and the results were critically compared. It was fairly observed that the reinforcement of FEF along with cellulose short fibres in the EPDM compounds has made a greater impact on improving the rheological properties and showed the synergistic effect between the fillers and the rubber matrix. The increase in temperature causes a decrease in the friction coefficient.